Suspek Difteri Tonsil Laring Pada Anak: Laporan Kasus - Suharyati, Titin; Herawati, Fauna; Fatmawati, Umi (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Diphtheria (DPT) is a disease caused by an infection of the bacterium Corynebacterium diphtheriae.Whereas Probable Diphtheria is a person with suspected Diphtheria plus one of the following symptoms: Had contact with a case (<2 weeks), incomplete immunization, including not having received a booster, residing in an endemic area of Diphtheria, Stridor, Bullneck, submucosal bleeding or petechiae on the skin, toxic heart failure, acute kidney failure, Myocarditis, death. This bacterium often infects the throat and nose. This bacterium produces toxins that can damage tissues and organs.The most characteristic symptom of diphtheria is the formation of a thick gray layer on the throat and tonsils. A 2-year-old child weighing 11 kg and measuring 85 cm tall presents with complaints of sore throat, swelling on the left side of the neck, fever, a breath that sounds like a snore when breathing, and a heavy voice during sleep. decreased food and drink intake. The patient was hospitalized in the Special Diphtheria Isolation Room in December 2024. History of using intermoxil injection, calmetasone injection, santagesic injection, and apetic syrup. Total Length Of Stay (LOS) for 10 days, with a family history of mumps. Received breast milk until the age of 2 years, complementary feeding until the age of 6 months, family food until the age of 1 year, developmental history of sitting with head upright at 6 months, able to roll over at 4 months, able to walk at 15 months, able to speak at 14 months, incomplete immunization history only up to DPT 1. Patient therapy PPC 900,000 IU, ADS 10,000 IU, dexamethasone, paracetamol tablet, D5 ¼ NS, RL, PPC 1.2 million IU. Diphtheria treatment is the most efficient effort to prevent the spread of Diphtheria. Nutritional status and malnutrition are closely related to diphtheria mortality. Keywords: Diphtheria, Tonsillitis, Immunization, Corynebacterium Diphtheriae, Children  ABSTRAK Difteri (DPT) merupakan penyakit yang disebabkan oleh infeksi bakteri Corynebacterium diphtheriae. Sedangkan Probable Difteri adalah orang dengan suspek Difteri ditambah dengan salah satu gejala berikut: Pernah kontak dengan kasus (<2 minggu), Imunisasi tidak lengkap, termasuk belum dilakukan booster, berada di daerah endemis Difteri, Stridor,Bullneck, pendarahan submukosa atau petechiae pada kulit, gagal jantung toxic, gagal ginjal akut, Myocarditis, meninggal. Bakteri ini sering menginfeksi bagian tenggorokan dan hidung. Bakteri ini menghasilkan toksin yang dapat merusak jaringan dan organ tubuh. Gejala difteri yang paling khas adalah terbentuknya lapisan abu-abu tebal pada tenggorokan dan amandel. Pasien anak 2 tahun berat badan 11 kg tinggi badan 85 cm dengan keluhan nyeri telan, bengkak leher sebelah kiri, demam, apabila bernapas nafas seperti mengorok, dan suara memberat saat tidur. makan minum berkurang. Pasien di rawat inap di Ruang Isolasi Khusus Difteri pada bulan Desember 2024. Riwayat penggunaan obat injeksi intermoxil, injeksi kalmetason, injeksi santagesic dan  sirup apetic. Total Length Of Stay(LOS) selama 10 hari, ada riwayat keluarga dengan mumps. Mendapatkan ASI sampai dengan usia 2 tahun, MPASI sampai usia 6 bulan, makanan keluarga sampai usia 1 tahun, riwayat tumbuh kembang duduk dengan kepala tegak pada usia 6 bulan, bisa tengkurap pada usia 4 bulan, bisa berjalan pada usia 15 bulan, dapat berbicara pada usia 14 bulan, riwayat imunisasi tidak lengkap hanya sampai DPT 1. Terapi pasien PPC 900.000 UI, ADS 10.000 UI,dexametason, paracetamol tablet, D5 ¼ NS, RL, PPC 1,2 juta UI. Pengobatan Difteri  merupakan upaya paling efisien mencegah penyebaran Difteri. Status gizi dan malnutrisi sangat berhubungan  dengan mortalitas Difteri.  Kata Kunci: Difteri, Tonsilitis, Imunisasi, Corynebacterium Diphtheriae, Anak